Sakti©: Secured Chatting Tool Through Forward Secrecy - Azni Hazlizan Ab Halim; Farida Hazwani Mohd Ridzuan; Nur Hafiza Zakaria; Abdul Alif Zakaria; Najwa Hayaati Mohd Alwi; Sakinah Ali Pitchay; Ismail Az-Zuhar; Ahmed A AlSabhany (Semarak Ilmu, 2024)
Indexed by Scopus